Salmonellosis control: the role of animal and product hygiene - WHO Expert Committee on Salmonellosis Control; World Health Organization(WHO) (Geneva: World Health Organization, 1988)
The WHO Technical Report Series makea a available the findings of various international groups of experts that provide WHO with the latest scientific and technican advice on a broad range of medical and public health subjects. Members of such expect groups serve without remuneration in their personal capacities rather than as representatives of governments or other bodies. An annual subcription to this series, comprising 12 to 15 such reports, costs Sw.fr.85.-.
Introduction -- Bacteriology, pathogenicity, and immunology of zoonotic salmonellae -- Epidemiology of zoonotic salmonella infection -- Veterinary contribution to salmonella surveillance -- Veterinary measures aimed at preventing the transmission of zoonotic salmonellae in farms -- Prevention of spread of salmonella contamination during slaughtering and processing -- Risks and hygiene when handling companion and other close-contact animals -- Preventive measures applied to internationak transfer of animals,feed,and food of animal origin -- Control of antibiotic resistance of zoonotic salmonellae -- Planning and management of the control of zoonotic salmonella infection in animals and food of animal origin -- Conclusion and general recommendation -- Recommendations for research